Coherent Mechanistic Patterns of Tropical Land Hydroclimate Changes. Issue 7 (10th April 2023) - Duan, Suqin Q.; Findell, Kirsten L.; Fueglistaler, Stephan A.
Abstract: Changes in tropical (30 S–30 N) land hydroclimate following CO2 ‐induced global warming are organized according to climatological aridity index (AI) and daily soil moisture (SM) percentiles. The transform from geographical space to this novel process‐oriented phase space allows for interpretation of local, daily mechanistic relationships between key hydroclimatic variables in the context of time‐mean and/or global‐mean energetic constraints and the wet‐get‐wetter/dry‐get‐drier paradigm. Results from 16 CMIP models show coherent patterns of change in the AI/SM phase space that are aligned with the established soil‐moisture/evapotranspiration regimes. We introduce an active‐rain regime as a special case of the energy‐limited regime. Rainfall shifts toward larger rain totals in this active‐rain regime, with less rain on other days, resulting in an overall SM reduction. Consequently, the regimes where SM constrains evapotranspiration become more frequently occupied, and corresponding hydroclimatic changes align with the position of the critical SM value in the AI/SM phase space. Plain Language Summary: Predictions of terrestrial hydroclimate changes (temperature, precipitation, evaporation, etc.) in a warming world rely largely on model simulations with often diverging results when presented in map view. Here, we introduce a process‐based phase space that organizes the spatial complexity by climatological aridity, and organizes the temporal complexity by daily soil moisture (SM). This allows for the analysis of model predictions in a comprehensive yet compact display which clearly reveals the connections between variables and mechanisms responsible for changes. Key results include the impact of SM limitation on elevated temperature extremes and the repartitioning of rainfall toward fewer, stronger events. This compact display is an efficient new tool for intercomparisons between models. The remarkably clean results suggest quantitative theoretical advances are possible despite the complexity of the system. Key Points: A novel process‐oriented phase space reveals coherent patterns of terrestrial hydroclimate change Patterns emphasize the impact of soil moisture on temperature extremes and the redistribution of rainfall toward more intense events Patterns of P − E changes reveal how land differs from the wet‐get‐wetter/dry‐get‐drier paradigm